Resolution of Legal Disputes Arising from Breach of Contract in Business Partnership Agreements - Iva Wanda Kusuma; Anik Tri Handayani; Angga Pramodya Pradhana (IHSA Institute, 2026)
This study aims to address the legal resolution of breaches of contract in business partnership agreements, particularly in business cooperative relationships between parties with contractual obligations. Partnership agreements are important legal instruments in modern economic activities because they regulate the rights and obligations of the parties and provide legal certainty in business relationships. However, in practice, contract breaches often occur and cause losses to one of the parties. This study employs a normative legal research method using a statutory approach and a conceptual approach through analysis of legal doctrines, legislation, and relevant court decisions. The results indicate that breach of contract in partnerships may take the form of failure to perform, delay in performance, or performance that does not conform to the terms of the agreement. These conditions can result in both material and immaterial losses for the aggrieved party. Under Indonesian civil law, the aggrieved party may seek compensation through dispute resolution mechanisms, whether through litigation or non-litigation. Therefore, the clarity of contract clauses and the agreed-upon dispute resolution mechanisms are crucial factors in providing legal certainty and preventing conflicts in business partnership relationships